Report on Conference on Islam And The Environment Oxford Centre For Islamic Studies Ditchley Park, 17-19 October, 2008 - Editor, The (KATHA- The Official Journal of the Centre for Civilisational Dialogue, 2018)
The conference, which was proposed an encouraged by HRH The Prince of Wales, was attended by scholars, religious, leaders, diplomats, environmental practitioners and policymakers from different parts of the world (Bangladesh, Egypt, India, Indonesia, Iraq, Kuwait, Malaysia, Oman, Qatar, Saudi Arabia, UK, US, Yemen), and representatives from major international agencies including the United Nation and World Bank. The participants were unanimous in their appreciation of the interest taken by HRH The Prince of Wales in the subject.